PENGUATAN LITERASI KEUANGAN DAN PEMAHAMAN STRATEGI PEMASARAN DIGITAL DALAM PENGGUNAAN E-WALLET DAN PAYLATER SISWA SEKOLAH MENENGAH ATAS - Lioni Indrayani; Putri Nilam Kencana; Luh Nadi Luh Nadi (LAP4B, 2026)
This community service program aims to improve digital financial literacy and understanding of digital marketing strategies among high school students at SMA Mulia Buana Parung Panjang. The program is based on the high use of e-wallets and paylater services among adolescents, which is not matched by adequate financial literacy. The method used is a participatory educational approach including interactive lectures, discussions, digital transaction simulations, and pre-test and post-test evaluations. The results show a significant improvement in students' understanding of financial management, paylater risks, and digital marketing strategies influencing consumer behavior. Students became more able to distinguish needs and wants and more critical toward digital promotions such as cashback, discounts, and influencer marketing. Evaluation results indicate an increase in all measured aspects. The program proves that financial literacy education is effective in shaping wiser financial behavior among students. In conclusion, strengthening financial literacy and digital marketing awareness is essential to build financially smart, critical, and responsible young generations in using financial technology.